Enhancing Customer Loyalty in Islamic Banking: The Role of Service Quality, Spiritual Marketing, and Customer Satisfaction (Study at BCA Syariah Yogyakarta Branch Office) - Putri Dwi Cahyani; Dwi Endra Prasetyo (Fundamental and Applied Management Journal, 2026)
This study examines how service quality and spiritual marketing enhance customer loyalty in Islamic banking through customer satisfaction as a mediating variable. Using a quantitative explanatory design, data were collected using SPSS. The results show that service quality positively affects customer satisfaction (β = 0.284; t = 3.046; p = 0.003), while spiritual marketing has a stronger effect (β = 0.400; t = 4.288; p < 0.001. Service quality and spiritual marketing also significantly influence customer loyalty, with respective effects of β = 0.188 (t = 3.125; p = 0.002) and β = 0.149 (t = 2.382; p = 0.019). Customer satisfaction emerges as the strongest predictor of loyalty (β = 0.657; t = 11.149; p < 0.001). The model explains 36,4% of customer satisfaction and 75,5% of customer loyalty. Sobel test results confirm that customer satisfaction significantly mediates the effects of service quality and spiritual marketing on customer loyalty. These findings emphasize that loyalty in Islamic banking is shaped by both functional service excellence and spiritually grounded marketing practices.